1971
DOI: 10.2134/agronj1971.00021962006300050010x
|View full text |Cite
|
Sign up to set email alerts
|

Response of Plant Water Potential to the Irrigated Environment of Southern Idaho1

Abstract: Laboratory studies have shown that plant water potential affects a number of key processes involved in growth, but there has been almost no information on what levels of water potential occur under irrigated conditions in the field. Before assessing the practical implication of laboratory results on soil and crop management, this type of information must be available. Consequently, plant water potential in irrigated crops of Zea mays, Triticum aestivum, Hordeum vulgaris, PhaseoIns vulgaris, Pisum sativum, Sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 14 publications
3
11
0
Order By: Relevance
“…Thus on a day receiving insolation at near maximal rates for this location, computed water potentials are of the same order as those measured by Millar et aZ. (1971) and Cary & Wright (1971). Presumably ear water potentials would fall below these values when water uptake is severely limited by soil water or when transpiration is accelerated by inputs of advected energy.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Thus on a day receiving insolation at near maximal rates for this location, computed water potentials are of the same order as those measured by Millar et aZ. (1971) and Cary & Wright (1971). Presumably ear water potentials would fall below these values when water uptake is severely limited by soil water or when transpiration is accelerated by inputs of advected energy.…”
Section: Discussionsupporting
confidence: 74%
“…J n wheat tillers with rolled leaves water potentials of ears and flag leaves were generally below -25 bars between 0900 and 1000 h. In other ears of wheat, water potentials below -25 bars were recorded, even though there were no signs of leaf rolling. Cary & Wright (1971) found that the daily range of water potential of irrigated wheat was between -10 and -35 bars with maxima ranging between -10 and -25 bars and minima as high as -15 bars and as low as -35 bars. The levels of plant water potential recorded in this 'Kopara' wheat and in Cary & Wright's were frequently lower than the water potentials at which net photosynthesis, leaf enlargement, and other growth processes slow to low rates in controlled environments (Boyer 1970;Frank et al 1973).…”
Section: Discussionmentioning
confidence: 96%
“…As the soils dried down during water stress (Figure 1), soil water potential decreased from approximately À 0.01 to À 0.6 MPa (moderate drought stress) and root and leaf water potentials further decreased from approximately À 0.4 to À 1.2 and approximately À 1.0 to À 1.6 MPa, respectively, in maize seedlings (Adeoye and Rawlins, 1981). Under field conditions, leaf water potentials in the range of À 0.5 to À 2.5 MPa are commonly seen for crop species (Cary and Wright, 1971). Leaf water potential can change significantly during the day, with maximum values in the morning and minimum values during the afternoon (Cary and Wright, 1971;Acevedo et al, 1979).…”
Section: Water Uptake and Loss In Cropsmentioning
confidence: 99%
“…In the dryland plots, differences of up to 4 bars were recorded in the upper canopy, but variations were less in the irrigated plots. Differences were probably associated with plant-toplant variability which Cary & Wright (1971) reported to be as high as 2-3 bars for field-grown wheat and barley. Short-term changes in radiation intensity, especially in mid canopy positions between successive measurements, would also increase measurement variability.…”
mentioning
confidence: 97%